Imperious Factors of Social Entrepreneurship to Create Innovative Ecosystems - A., Poornima; G., Dr.Rajini (The journal of contemporary issues in business and government, 2021)
Back Ground: India has gained demographic advantage due to its youth population. There is a need to channelise working-age population to choose right career in order to contribute to our economy which could be done by Educational institutions. Objectives: To identify the important variables associated with innovative ecosystem. To analyse the relationship between innovative ecosystem and social vision, social entrepreneurial intention. Methodology: Multistage sampling method was used to locate the students from various higher educational institutions in India. Survey questionnaire was used to collect data. SPSS 26.0 is used to analyse the data. Correlation, factor analysis, Multiple regression was used in the study. Findings: social vision, social intelligence, self- awareness, social entrepreneurial intention, informal network support, and innovative ecosystem are the factors evolved. Discussion: Higher educational institutions could create an innovative ecosystem to support students to take social entrepreneurship as their career choice.